Operation time and clinical outcomes for open infrarenal abdominal aortic aneurysms to remain stable in the endovascular era - Gruber, M.; Sotir, A.; Klopf, J.; Lakowitsch, S.; Domenig, C.; Wanhainen, A.; Neumayer, C.; Busch, A.; Eilenberg, W. (Frontiers in Cardiovascular Medicine, 2023)
Objective: Endovascular aortic repair (EVAR) has become a routine procedure in many areas of the world. Ultimately, the increasing number of EVAR cases entails changing conditions for open surgical repair (OSR) regarding patient selection, complexity and surgical volume. This study aimed to assess time-trends of open abdominal aortic aneurysm (AAA) repair in a high-volume single-center in Austria over a period of 20-years, with a focus on operating time and clinical outcome. Material and Methods: A retrospective analysis of all patients treated for infrarenal AAA with OSR or EVAR between January 2000 and December 2019 was untertaken. Infrarenal AAA was defined by the presence of > 10 mm aortic neck. Cases with ruptured or juxtarenal AAA were excluded from the analysis. Two cohorts of patients treated with OSR at different time periods -2000-2009 vs. 2010-2019 -were assessed with regards to demographical and procedure details as well as clinical outcome. Time periods were defined based on increasing single-center trend towards EVAR approach from 2010 onwards. Results: A total of 743 OSR and 766 EVAR were performed. 589 of OSR cases were infrarenal AAA. EVAR to OSR ratio was stable around 50:50 over time (p=0.488). History of coronary arterial bypass (13.4 vs. 7.2%, p=0.027), coronary artery disease (38.1 vs. 25.1%, p=0.004), peripheral vascular disease (35.1 vs. 21.3%, p=0.001) and smoking (61.6 vs. 34.3%, p<0.001) decreased significantly after 2010. Age decreased from 68 to 66 years (p=0.023). The operating time for OSR remained stable (215 vs. 225 min, first vs. second time period, respectively, p=0.354). Intraoperative (5.8 vs. 7.2%, p=0.502) and postoperative complication rates (18.3 vs. 20.8%, p=0.479) remained stable as well. The 30-day mortality rate did not change over both time periods (3.0 vs. 2.4%, p=0.666).Balanced EVAR to OSR ratio, similar complexity of cases as well as volume over the two decades in OSR show stable OSR time without compromise in clinical outcome.